ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSITAS R&D PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Budi Chandra,; Naomi Marsaulina H, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This study tested the foreign ownership, managerial ownership, government ownership, financial distress, board size, growth, age of firm, return on assets, leverage, and firm size against the Intensity of R&D. From this study used 106 companies, the equivalent of 530 samples listed on the Indonesia Stock Exchange from period 2013-2017. This study applies the purposive sampling method. The data obtained from the data used in the financial statements of the company which published on the website www.idx.co.id. The sample taken in this study are all types of companies that have criteria according to research needs, especially those that have R&D expenditure accounts. The results on this research show that the government ownership and board size has a significant negative effect on the R&D intensity, while the foreign ownership, managerial ownership, financial distress, and growth does not have a significant effect on the R&D intensity